THE EFFECT OF VARIOUS TISSUE EXTRACTS UPON THE GROWTH OF ADULT MAMMALIAN CELLS IN VITRO - Walton, Albert J. (The Rockefeller University Press, 1914)
The cultivation of cells in vitro affords a valuable means of estimating the effects of tissue extracts. Tissue extracts have a definite effect upon the growth of adult mammalian cells in vitro. The majority of tissue extracts stimulate the growth of connective tissue, but liver extract inhibits it. The extracts are to a certain extent specific in their action upon the growth of parenchymatous cells. Some cells are stimulated by one extract and inhibited by another, and those extracts which inhibit one type of parenchymatous cell may stimulate another type. Homogenous and autogenous extracts are equally efficacious in their action upon the growth of cells. The extracts may be preserved for a short period of time without suffering any change in their power of affecting the growth of cells.